Regenerating Youth Development through Entrepreneurship - Raja Suzana, Raja Kasim; Azham, Zulkharnain; Zulazli, Hashim; Wan Nursafiah, Wan Ibrahim; Sophie Eliza, Yusof (Elsevier Ltd., 2014)
In Malaysia, there are 13.3 million, of youth who are between ages of 15-40, and they represent 46% of the total Malaysian population. Of this, 4.5 millions of youth populations are between these ages of 15-25 categories and regardless either they live in urban and rural communities; there appears to be approximately 25% who are vulnerable and they are potential to be at-risk youth. Build on past empirical studies, these at-risk youths may be those that come from families who are not emotionally supportive, lacking parental supervision on activities that they are involved in, deficient in social skills, low aspiration, emotional control and self esteem, from low-waged family, unsatisfactory living condition, peer influence and devoid of suitable role model. This paper is aimed to review global trends and practices from past research on regenerating youth development through entrepreneurship. The focused is merely to help to resolve Malaysian youth issues that could enhance their quality of life and participate fully in the development of society and the nation on a whole. Youth living in the marginalized communities are also facing a pervasive unemployment. In this paper, intervention empowerment programs were proposed for youth living in the marginalized communities towards positive youth development. It also highlights the importance of strengthening the mechanisms for sustainability and, eventually, to recommend effective mechanism in enhancing youth living in the marginalized communities to be mainstreamed appropriately.